2015
DOI: 10.1186/s12883-015-0413-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving medication adherence in stroke patients through Short Text Messages (SMS4Stroke)-study protocol for a randomized, controlled trial

Abstract: BackgroundStroke is a major cause of morbidity and mortality, especially in low and middle income countries. Medical management is the mainstay of therapy to prevent recurrence of stroke. Current estimates are that only 1 in 6 patients have perfect adherence to medication schedules. Using SMS (Short Messaging Service) as reminders to take medicines have been used previously for diseases such as diabetes and HIV with moderate success. We aim to explore the effectiveness and acceptability of SMS in increasing ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Following is a brief outline of the methodology used in the study. For further details and access to questionnaires and tools, please refer to our paper on trial methods [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following is a brief outline of the methodology used in the study. For further details and access to questionnaires and tools, please refer to our paper on trial methods [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…We sought to determine the effectiveness of customized SMS reminders plus Health information SMS in addition to usual care in adult stroke patients compared to usual care only in improving medication adherence at a hospital stroke service in Pakistan. In addition we explored the biologic effects if any, on blood pressure for those who received SMS and the scalability characteristics of the innovation based on Rogers Diffusion of Innovation Theory derived questionnaire that measures intervention qualities such as Simplicity, Compatibility, Observability and Relative advantage [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any 1-point shift is a clinically important increase in scores. In addition, in a study carried out locally, we have shown the use of IT-based interventions to have effects on this score in these ranges [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent review suggest various levels of health literacy exists across countries and significant improvement is needed at government level (30). E and M-health technologies may help to improve patients' understanding of medicines and thus improve medication compliance (31). However, evidence of use of such technologies in this manner -remains conflicted (32,33).…”
Section: Discussionmentioning
confidence: 99%